1998
DOI: 10.1016/s0005-2728(97)00087-x
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocyanide-peroxidase activity of cytochrome c oxidase

Abstract: Redox interaction of mitochondrial cytochrome c oxidase (COX) with ferrocyanide/ferricyanide couple is greatly accelerated by polycations, such as poly-l-lysine [Musatov et al. (1991) Biological Membranes 8, 229-234]. This has allowed us to study ferrocyanide oxidation by COX at very high redox potentials of the ferrocyanide/ferricyanide couple either following spectrophotometrically ferricyanide accumulation or measuring proton uptake associated with water formation in the reaction. At low [ferrocyanide]/[fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1999
1999
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…It has been demonstrated that CcO can undergo a ' peroxidaselike ' reaction at its haem a $ -Cu B binuclear centre, a reaction that has a high K m for H # O # with participation by compound P and compound F intermediates [15,16]. We have employed the ESR spin-trapping technique to investigate the oxidative damage induced in CcO by H # O # [17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that CcO can undergo a ' peroxidaselike ' reaction at its haem a $ -Cu B binuclear centre, a reaction that has a high K m for H # O # with participation by compound P and compound F intermediates [15,16]. We have employed the ESR spin-trapping technique to investigate the oxidative damage induced in CcO by H # O # [17].…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme functions to reduce dioxygen to H 2 O at the active center of heme a 3 -Cu B and couples proton pumping across the mitochondrial inner membrane to provide the driving energy for ATP synthesis (19). It has been reported that a peroxidase-like reaction can occur at the heme a 3 -Cu B center of CcO with a very high K m for H 2 O 2 (20,21). The addition of excess H 2 O 2 can oxidize CcO to yield a peroxy intermediate (or "compound P"), and a one-electron reduction of compound P with either ferrocyanide or cytochrome c yields the ferryl-oxo species (or "compound F").…”
mentioning
confidence: 99%
“…It was shown [32] that the presence of H2O2 enables CcO to operate within a truncated peroxidase cycle bypassing the eu-oxidase phase of the reaction. The reaction of CcO with excess hydrogen peroxide results in the sequential formation of oxoferryl intermediates which are similar in structure to the intermediates FI-607 and FII-580 registered in the oxygen reduction cycle by the rapid kinetic techniques (see reviews [1,2,7,33]).…”
Section: The Effects Of Thyroid Hormones On the Cco Partial Activities Associated With The Peroxidase Phase Of Catalytic Cyclementioning
confidence: 99%
“…As demonstrated in [32], aerobic registration of the peroxidase activity of CcO requires highpotential (Е0  +400 mV) electron donors. Oxidation of such compounds is possible due to the participation of oxoferryl intermediates FI-607 and FII-580 as final acceptors since their one-electron redox transitions are characterized by Е0' around 1 V [35,36].…”
Section: Thyroid Hormones Do Not Inhibit the Cco Peroxidase Activitymentioning
confidence: 99%